Modelagem para a mensuração da evasão de unidades consumidoras das distribuidoras de energia elétrica - Nascimento, Felipe Moraes do (2020)
In recent years, the spread of distributed photovoltaic generation has played a fundamental role in the face of political, economic, and environmental issues in the electricity sector. One of these issues is its relationship with energy distributors, which has been presenting some complications due to the high penetration of distributed generation in the network, or what is caused by threats to the distribution system operators. Electricity distributors operate at economies of scale and the high penetration of distributed photovoltaic generation makes these companies lose part of their revenue, in addition to other effects such as increased costs, increased tariffs and influence for the avoidance of other items beyond technical issues. The increase in the diffusion of photovoltaic energy is due both to the decline in technology costs and the support policies adopted worldwide. However, the growth of the share of photovoltaic energy in the energy matrix is a complex process since the effective adoption of innovation involves several interconnected factors. This work seeks to develop a model to measure the probability of evasion of consumer units for distributed photovoltaic generation, for this purpose, to systematically assess the critical factors that can influence the distribution system operators in measuring the evasion of their tests used in technology photovoltaic. In addition, to achieve the research objectives, a case study was carried out in which 20 consumer units were analyzed, the results indicated for the modeling are adequate for the development of diagnoses of probability of evasion by units of consumer for a distributed photovoltaic generation, considering the Brazilian scenario, forming auxiliaries as distribution companies in decision making, using a reduction of the impacts caused by the diffusion of this technology. Thus, the study also contributes to the planning of studies on the electrical system, with theoretical, political, and practical implications for developing countries and regions of countries where the presence of photovoltaic systems is still incipient.